Validitas dan Realibilitas Instrumen Teori Pilihan Karir Holland di Indonesia - Anggraini, Weni; Kurniawan, Fandy; Susilawati, Susilawati; Hasna, Afra (Kuras Institute, 2020)
Validity and reliability are the main topics in every research instruments. It is important how to create research instrument that is connected to the construct being measured. In this article, the authors tested the validity and reliability of Holland's career instrument Indonesian version. The participants involved are in the period of career preparation and choice, within an educational institution or a job, but has not yet had satisfaction with their career. The participants' age range from 15 to 27 years. The validity test is carried out using the conventional validity type, where the item is declared valid if the correlation coefficient is ≥ 0.3. The results showed 43 items were declared valid and 5 items were declared invalid while the reliability coefficient found is 0.906. Based on the results, Holland's career instrument Indonesian version in a good instrument to measure career preparation and career choice.